Role of p42/p44 mitogen-activated-protein kinase and p21(waf1/cip1) in the regulation of vascular smooth muscle cell proliferation by nitric oxide - Bauer, Philip M. (The National Academy of Sciences, 2001)
The purpose of this study was to determine the involvement of the p42/p44 mitogen-activated protein kinase (MAPK) pathway and induction of p21(waf1/cip1) in the antiproliferative effects of nitric oxide (NO) on rat aortic smooth muscle cells (RASMC). NO, like α-difluoromethylornithine (DFMO), interferes with cell proliferation by inhibiting ornithine decarboxylase (ODC) and, therefore, polyamine synthesis. S-nitroso-N-acetylpenicillamine or (Z)-1-[N-(2-aminoethyl)-N-(2-aminoethyl)-amino]-diazen-1-ium-1,2-diolate inhibited RASMC growth at concentrations as low as 3 μM, and DFMO elicited effects at concentrations of 100 μM or greater. The cytostatic effect of NO and DFMO was prevented by the MAPK kinase 1/2 inhibitors PD 098,059 or U0126. This finding suggests that the p42/p44 MAPK pathway is involved in the inhibition of RASMC proliferation by NO. Western blot analysis revealed that treatment of RASMC with NO or DFMO leads to activation of p42/p44 MAPK and induction of p21(waf1/cip1). This effect was prevented by MAPK kinase 1/2 inhibitors, suggesting that induction of p21(waf1/cip1) depended on activation of p42/p44. Moreover, activation of p42/p44 and induction of p21(waf1/cip1) were prevented by exogenous putrescine but not ornithine, suggesting this effect was due to the inhibition of ODC by NO or DFMO. Finally, activation of p42/p44 MAPK and induction of p21(waf1/cip1) were cGMP-independent. Neither 1H-(1,2,4)oxadiazolo[4,3-α]quinoxalin-1-one nor zaprinast influenced the cytostatic effect of NO or DFMO or their ability to activate these signal transduction pathways. These observations suggest that inhibition of ODC and accompanying putrescine production are the underlying mechanisms by which NO and DFMO activate the MAPK pathway to promote induction of p21(waf1/cip1) and consequent inhibition of cell proliferation.